INFOLIBRIS – REVISTĂ DE PROMOVARE A CULTURII SCRISE - Caciuc, Natalia (CEP USM, 2013)
I proposed a cultural journals written in the title InfoLibris. Magazine aimed first of all written culture professionals, who are interested popularization book promotion and closer to the public. Instead InfoLibris journal can become the ideal meeting place of supply and demand, and take the pulse of the market barometer written culture in a more objective manner, providing publishers, journalists and readers to debate the best opportunity , to display their competitive advantages, to promote and inform all times.
Keywords: presa scrisă